Pulmonary Doppler Notch Pattern in Relation with Pulmonary Vascular Resistance Index in Patients with Atrial Septal Defect - Nurnajmia Curie Proklamartina; Radityo Prakoso; Oktavia Lilyasari; Rina Ariani; Sisca Natalia Siagian; Amiliana Mardiani Soesanto (The Indonesian Heart Association, 2020)
Background: Atrial septal defect (ASD) potentially causes pulmonary hypertension (PH) and increased pulmonary vascular resistance (PVR). In previous studies, pulmonary Doppler notch was evident in patients with high PVR. There was a distinct notch pattern in different types of PH. This study aims to examine whether echocardiographic notch pattern could estimate PVR in secundum ASD patients. Methods: Cross sectional study was conducted in secundum ASD patients ≥18 years old who underwent clinically indicated right heart catheterization. Association of notch presence and PVR index (PVRi) and correlation of notch ratio (NR), a parameter of notch location, and PVRi were analyzed. The best cut off of NR value was obtained using the receiver operating characteristics curve. Results: Among 60 patients, the notch was present in 50 patients (83%) and significantly associated with PVRi ≥6 WU.m2 (p<0.0001). Notch ratio and PVRi had a moderate negative correlation (r=-0.410, p=0.003). Receiver operating characteristics curve with area under curve 0.709 showed that cutoff NR value of 1.635 was a good discriminator for PVRi ≥6 WU.m2, with 70% sensitivity, 70% specificity, 56.8% positive predictive value, and 14.9% negative predictive value. Patients were then classified into three groups of notch pattern based on its presence and location, which was significantly associated with PVRi (p<0.0001). Conclusions: Pulmonary Doppler notch pattern is associated with PVRi in secundum ASD patients. This may be used clinically to estimate PVR to aid patient selection for further invasive investigation. Keywords: atrial septal defect, Doppler echocardiography, notch, notch ratio, pulmonary vascular resistance